Contribution of Imaging in the Diagnosis of Cholangiocarcinoma in Choledochal Cyst - Djivèdé Witchékpo Maurice Mohamed Akanni; Kouassi Paul N’zi; Kofi-Mensa Savi de Tové; Laura Petrovai (Case Reports in Radiology)
The choledochal cyst is a rare congenital malformation of the bile ducts. It is considered as a precancerous state. The incidence of cancer in choledochal cyst increases with age and occurs around 32 years old. Therefore, young adults are often involved. In adults, clinical signs are rare and unspecific. We are reporting here the case of a cholangiocarcinoma in choledochal cyst in young adult diagnosed by ultrasonography, CT scan, and MRI and confirmed by histopathological examination.